Honokiol Downregulates Kruppel-Like Factor 4 Expression, Attenuates Inflammation, and Reduces Histopathology After Spinal Cord Injury in Rats. Issue 6 (15th March 2015) - Liu, Jia; Zhang, Changmeng; Liu, Zhi; Zhang, Jianzheng; Xiang, Zimin; Sun, Tiansheng
Abstract : Study Design: Randomized experimental study. Objective: To investigate the neuroprotective effect of honokiol (HNK) on rats subjected to traumatic spinal cord injury (SCI) and the molecular mechanisms. Summary of Background Data: Inflammation contributes to the secondary injury to the spinal cord. Honokiol has been used as a neuroprotective agent because of its strong antioxidant and anti-inflammatory properties. Kruppel-like factor 4 (Klf4) is a newly identified critical target for the anti-inflammatory effect of HNK. Whether HNK can inhibit inflammatory response in rat model of SCI through mediating the expression of Klf4 has yet to be elucidated. Methods: Eighty-four adult female Sprague-Dawley rats were randomly divided into 4 groups as sham, SCI, SCI + Vehicle (0.1% propylene glycol in saline, intraperitoneally), and SCI + HNK (20 mg/kg, intraperitoneally) groups. The influences of HNK on the proinflammatory cytokines, microglial activation, neutrophil infiltration, histological changes, and improvement in motor function were assessed. Results: In the SCI group, proinflammatory cytokines, microglial activation, neutrophil infiltration, and Klf4 expression levels were increased compared with the sham group ( P < 0.001). HNK intervention downregulated the expression of Klf4, reduced the production of proinflammatory cytokines, inhibited microglial activation, and neutrophil infiltration ( P < 0.05). Furthermore, HNK also reduced histopathology and improved functional outcome after traumatic SCI. Conclusion: HNK reduces secondary tissue damage and improves locomotor function recovery after SCI through suppressing inflammatory response, and can be used as a potential therapeutic agent for SCI. Level of Evidence: NA Abstract : Short-term influences of Honokiol on the inflammatory response, histopathology, and locomotor function in rats subjected to traumatic spinal cord injury were evaluated. Honokiol contributes to reducing secondary tissue damage and improve functional outcome after spinal cord injury, and may be used as a potential neuroprotective agent against spinal cord injury in the future.